Clinical practice guidelines for the management of atopic dermatitis 2018. Issue 12 (9th October 2019) - Katoh, Norito; Ohya, Yukihiro; Ikeda, Masanori; Ebihara, Tamotsu; Katayama, Ichiro; Saeki, Hidehisa; Shimojo, Naoki; Tanaka, Akio; Nakahara, Takeshi; Nagao, Mizuho; Hide, Michihiro; Fujita, Yuji; et al.
Abstract: Atopic dermatitis (AD) is a disease characterized by relapsing eczema with pruritus as a primary lesion. The current strategies to treat AD in Japan from the perspective of evidence‐based medicine consist of three primary measures: (i) the use of topical corticosteroids and tacrolimus ointment as the main treatment for the inflammation; (ii) topical application of emollients to treat the cutaneous barrier dysfunction; and (iii) avoidance of apparent exacerbating factors, psychological counseling and advice about daily life. The guidelines present recommendations to review clinical research articles, evaluate the balance between the advantages and disadvantages of medical activities, and optimize medical activity‐related patient outcomes with respect to several important points requiring decision‐making in clinical practice.